Exponential Tapered Balun with Different Sizes for UWB Elliptical Dipole Antenna - M A Zakwan; S A Hamzah; S M Shah; K N Ramli; M S Zainal; L Audah; N Abdullah; A Ubin; F C Seman; A K Anuar; Adeeb Salh; M Esa; N N N Abd Malik (Universitas Ahmad Dahlan, 2018)
This work presents a broadband tapered balun with different sizes using nonlinear transition particularly suitable for planar and three-dimensional (3-D) dipole antennas for ultra-wideband (UWB) applications such as communication, radar systems and geolocation precision. Four baluns with wideband microstrip-to-parallel-strip transition using an elliptical structure for an elliptical dipole antenna are proposed. The initial balun structure consists of a nonlinear profile with a quarter-wavelength for both height and width. By studying the current distributions at the balun surface, it can be reduced to 25%, 50% and 75% from the original size. Measured results based on the reflection coefficients for all baluns are shown to be better than -10 dB from 1.0 GHz to 10 GHz. These baluns are integrated with an elliptical dipole which acts as a feeding circuit. Eight set of antennas with a planar and 3-D configurations with four different sizes are proposed in this work. The planar configurations are named as Planar 1, Planar 2, Planar 3 and Planar 4 while the 3-D configurations are named as 3D Dipole 1, 3D Dipole 2, 3D Dipole 3 and 3D Dipole 4, respectively. The results show that all antennas with the proposed baluns operates within the UWB frequency range.